Research Paper on Secondary Bacterial Infection in Tuberculosis Patient: Clinical features and treatment of secondary bacterial infections in tuberculosis patients (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bacterial infections is one of the most important complications in the patients with pulmonary tuberculosis. We reported the causative microorganisms in these cases with special reference to various clinical features and presented the recommended treatment and prophylaxis against respiratory bacterial infections in the patients with pulmonary tuberculosis sequelae. In 1988 and 1989, 63 patients with tuberculosis sequela were demonstrated to have been infected with respiratory pathogenic bacteria by the quantitative sputum culture method (greater than or equal to 10(7)ml) in Tokyo National Chest Hospital. The malefemale ratio of these patients was 3.5, and their average age was 62.5 years. Causative microorganisms of the secondary infections in the patients with tuberculosis sequela were essentially similar in those with other lower respiratory tract infections, i.e., chronic bronchitis, bronchiectasis, diffuse panbonchiolitis, chronic pulmonary emphysema, etc. Pseudomonas aeruginosa, other glucose-nonfermentative Gram-negative bacilli (GNF-GNB), and glucose-fermentative Gram-negative bacilli (GF-GNB) were the major pathogenic bacteria responsible for the chronic respiratory failure andor fatal outcome in the post-tuberculous patients. Patients with complications, including aspergillosis, atypical mycobacteriosis, bronchial asthma, and so forth, showed no specific causative microorganism for the secondary infections except frequent isolation of Haemophilus influenzae. Our clinical observations clearly demonstrated that there were differences between the causative microorganisms in patients hospitalized during 1988 to 1989 and those in patients without admission. Gram-negative bacilli, including P. aeruginosa, GNF-GNB and GF-GNB, and Staphylococcus aureus were predominant in hospitalized patients. On the contrary, Streptococcus pneumoniae, H. influenzae, and Branhamella catarrhalis were major pathogenic bacteria in patients without hospitalization.